Urban anthropology from theorizing to institutionalization - Nouichi, Ouarda (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This study is considered as a conceptual introduction to urban anthropology, which is a descriptive and analytical theoretical study aimed at identifying the concept and fields of urban anthropology, the factors of interest in this discipline and highlighting the historical process of its origin and development in terms of theory and methodology, to establish this science as a science and academic specialization within the disciplines of general anthropology and its contributions to urban studies and its methodological problems, through giving a glimpse of the reality of urban anthropology in the Arab world, including Algeria. Urban anthropology-which deals with the study of subculture in cities and urban problems, especially the problems of migration and urban and cultural adaptation - has gone through several stages, beginning with the first attempts of the first anthropological researchers, headed by Robert Radfield and Nash Warner in the study of urban community anthropological study. multiple factors have helped in the interest of this type of studies and the development of theories and approaches the West. We have come to the conclusion that the foundation of urban anthropology came based on the importance of Urban Studies in the field of anthropology to understand many urban phenomena, including urbanization and multiculturalism within cities, so it was necessary the emergence of the discipline of urban anthropology, the latter passed through stages and levels of study from ethnography, i.e. description to Ethnology, i.e. description and analysis, and it was not easy to find solutions to the methodological and theoretical problems that faced researchers at the beginning of their urban studies, approaches, techniques and theories were borrowed from other urban disciplines,